Study of cord blood lipid profile at birth and its relation to gestational maturity and birth weight - Gupta, Rashmi; Goyal, Alpana; Gupta, Madhuri (Asian Journal of Medical Sciences, 2021)
Background: Dyslipidemia is attributed for coronary artery diseases. Early detection of dyslipidemia in neonatal cord blood could help to identify possible future risk factors of coronary artery diseases in new born. Aims and Objectives: This study was undertaken to compare lipid profile of small for gestational age (SGA) or preterm and appropriate for gestational age (AGA) or near-term neonates. Material and Methods: A total of 60 neonates were included; of which 33 were AGA and 27 SGA neonates. 2 ml of blood was obtained from the umbilical vein immediately after cord clamping at delivery from each subject and kept in a plain vial, after the serum separation analyzed for biochemical parameters. Results: In SGA neonates, mean TC (total cholesterol), TG (triglycerides) LDL (low density lipoprotein cholesterol), HDL (high density lipoprotein cholesterol) and triglycerides were 66.60±17.76 mg/dl,57.32±23.7 mg/dl, 54.06±20.11 mg/dl, 19.06±17.03mg/dl respectively. SGA neonates had more TC, TG and LDL than AGA neonates (P<0.05). There was significant difference in mean lipid profile between preterm andnear-term neonates. Thus, lipid profiles in SGA neonates in thisstudy are higher than that of AGAneonates. Conclusion: It can be concluded that preterm babies are exposed to more hypercholesterolemia and potentially more atherogenic environment than their term counterparts.